(untitled) (Tanzania Medical Journal, 2017)
IntroductionNeurocysticercosis (NCC) is the most common parasitic infection of the central nervous system (CNS)(1)(2). It is caused by larvae stages of Taenia Solium and is the major cause of acquired epilepsy worldwide(3). Seizure disorders are common neurological manifestation(4); however, neuropsychiatric manifestations have also been reported(5,6). Humans acquire infection through ingestion of eggs of Taenia Solium from contaminated food(7). The brain immunological response towards the cysts may be responsible for the pleomorphic manifestations(8), including psychiatric symptoms that may take years before the onset of seizures(6). As a result, diagnostic confusion is common, and this often affects management and outcome.Case reportWe report a case of 30-year-old black African male who presented with a history of auditory hallucinations and behavioral changes without focal neurologic signs or symptoms. The onset of generalized tonic-clonic seizures prompted him to seek medical attention although prodromal psychiatric symptoms started about a year before the onset of seizures. MRI of the brain revealed multiple cysts involving mainly the cerebral cortex.ConclusionThis case highlights the need to exclude organic cortical pathology should in rare forms of psychiatric manifestations such unilateral auditory hallucinations and acute behavioral disturbances. Correct diagnosis and prompt management will prevent complications and usually have a favorable prognosis.Key clinical messagePleomorphic manifestations of NCC pose a challenge in diagnosis. We present a case of a 30-year old male who presented with prodromal psychiatric symptoms before the onset of generalized tonic-clonic seizures. This case highlights challenges in diagnosis though prompt management promises a favorable outcome.